2002
DOI: 10.1557/proc-715-a26.1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Light-induced Enhancement of Open-Circuit Voltage and Structural Change of Heterogeneous Silicon Solar Cells

Abstract: We observe a significant light-induced increase in the open-circuit voltage, Voc, of thin-film silicon solar cells whose intrinsic (i) layer consists of an amorphous and microcrystalline mixed phase. The increase depends on the i-layer thickness, the i-layer deposition temperature, the initial Voc values, and the light-soaking intensity. An increase of as large as 150 mV is observed. The original Voc is restored after subsequent thermal annealing. In-situ photoluminescence (PL) spectroscopy is used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…1), is related to the diffusion of molecular hydrogen, resulting in a reduction of active solar cell area due to delamination. However such delamination can hardly account for the observed increase in V oc , which in the literature has been related to dissociation of B-H complexes [18], hydrogen evolution from nanocrystals [21], and light-induced defect states re-distribution at p/i interface [22].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…1), is related to the diffusion of molecular hydrogen, resulting in a reduction of active solar cell area due to delamination. However such delamination can hardly account for the observed increase in V oc , which in the literature has been related to dissociation of B-H complexes [18], hydrogen evolution from nanocrystals [21], and light-induced defect states re-distribution at p/i interface [22].…”
Section: Discussionmentioning
confidence: 92%
“…Various hypothesis have been proposed to explain the increase in V oc : (i) the activation of boron in the p-layer of the solar cells during light-soaking [4,[13][14][15][16][17][18], (ii) light-induced changes in the intrinsic mixed-phase material [19][20][21] and (iii) decrease in valence band tail and state re-distribution at p/i interface [22]. Most of those studies deal with solar cells based on a-Si:H materials deposited by dissociating silane-hydrogen gas mixtures, while our standard a-Si:H was deposited by dissociating pure silane.…”
Section: Evolution Of the Solar Cell Parameters As A Functionmentioning
confidence: 99%
“…We controlled the hydrogen dilution ratio so that the films were deposited in the amorphous/nanocrystalline transition regime. We were able to obtain various material structures from a single deposition on the same substrate: amorphous (from the center of the substrate), mixed-phase (along the edges of the substrate), and a high nanocrystalline volume fraction (near the four corners), as previously reported [8,9,14,15]. We deposited many samples with different hydrogen-dilution ratios and different P-doping levels and found that adding PH 3 in the gas phase significantly increased the hydrogen-dilution threshold required for reaching the amorphous/nanocrystalline transition.…”
Section: Doping Effect On the Materials Structure In Mixed-phase Si:h mentioning
confidence: 65%
“…We controlled the deposition parameters in the regime of amorphous to nanocrystalline transition to obtain various material structures on one substrate, such as the center of the deposition showing an amorphous structure, edges with a mixed-phase signature, and the corners with a substantially nanocrystalline volume fraction as previously reported [14,15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation